Religious Coping in Students with Disabilities with Disabilities - Alia, Noor Anifatul (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2022)
Education is a right that must be obtained by everyone without exception, as well as people with disabilities, they have the right to receive education according to their abilities, whether formal education or non-formal education, general knowledge or religious knowledge, and it is their choice to determine what path of education they take. what they take is like students with disabilities who study at Islamic boarding schools. This is an unusual phenomenon because students with disabilities have to struggle like normal students in general with their limitations. In this research, students with disabilities admitted that they were hampered by several things, namely adjustment, independence and bullying from friends. This research aims to explore religious coping in students with disabilities who are physically impaired. The research method used in this research is a qualitative research method with a phenomenological approach. Data collection used in this research was interviews and observations. The data validity technique uses triangulation techniques. The results of the research in this study were that students with disabilities were able to accept and be sincere about their situation, the subject decided to receive Islamic boarding school religious education on the basis of religion, he wanted to deepen his knowledge of religion, and this was done through the Islamic boarding school route. The religious coping strategy used by the subject is the deferring approach carried out by the subject by surrendering or believing that there will definitely be help from God, and the collaborative approach carried out by the subject by taking lessons from each problem and trying to solve it by asking God for help. Apart from that, the subjects also used a form of positive religious coping, where the researchers found that the subjects reflected with feelings of patience, gratitude and sincerity. Subjects also need support, the biggest support comes from parents, then from friends and the surrounding environment.